Equity Crowdfunding sebagai Opsi Penyelamatan UMKM dari Krisis Akibat Pandemi - Nibras Anny Khabibah; Risma Wira Bharata (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2021)
This study aims to identify the role of equity crowdfunding in saving MSMEs from the crisis due to the pandemic. This study used a qualitative descriptive method using various sources of information from previous research, regulations, and published repot by various agencies such as OJK and Kemenkopukm. The Covid-19 pandemic that entered Indonesia resulted in a drastic decrease in the profits of MSME business players. This makes MSMEs have to carry out various strategies to maintain their business so they are not swept away by a pandemic storm. Reducing workforce, saving sales figures using online platforms, and pivoting are some of the strategies undertaken by MSMEs to maintain their business. This makes MSMEs need to take their business through the addition. Equity crowdfunding is an option for MSMEs to increase capital to carry out various rescue strategies. In addition to providing opportunities for MSMEs to get additional funds, through the equity crowdfunding platform, MSMEs can also support their business to the wider community. This can increase the value of products and brands and increase the popularity of the customer base so as to increase the MSME business value.